Association between allergic rhinitis and asthma control in Peruvian school children: a cross-sectional study. - Padilla, Justo (2013)
Background. Asthma and allergic rhinitis are highly prevalent conditions that cause major illness worldwide. This study aimed to assess the association between allergic rhinitis and asthma control in Peruvian school children. Methods. A cross-sectional study was conducted among 256 children with asthma recruited in 5 schools from Lima and Callao cities. The outcome was asthma control assessed by the asthma control test. A score test for trend of odds was used to evaluate the association between allergic rhinitis severity and the prevalence of inadequate asthma control. A generalized linear regression model was used to estimate the adjusted prevalence ratios of inadequate asthma control. Results. Allergic rhinitis was present in 66.4% of the population with asthma. The trend analysis showed a positive association between allergic rhinitis and the probability of inadequate asthma control (). It was associated with an increased prevalence of inadequate asthma control, with adjusted prevalence ratios of 1.53 (95% confidence interval: 1.19−1.98). Conclusion. This study indicates that allergic rhinitis is associated with an inadequate level of asthma control, giving support to the recommendation of evaluating rhinitis to improve asthma control in children.